Гальмівні ефекти гетерополіядерних комплексів Сu(ІІ)/Co(ІІІ) з діетаноламіном на секрецію жовчі у щурів - Синельник, Т.Б.; Весельський, С.П.; Кокозей, В.М.; Маханькова, В.Г.; Рибальченко, Т.В. (Видавничий дім "Академперіодика" НАН України, 2008)
We investigated heteropolynuclear copper (II) and cobalt (III) complexes with diethanolamine intraportal infusion effects on the bile and bile acid secretion and their biotransformation in rats. It is established that the substances decreased the bile secretion due to the tauroconjugated bile acid secretion decrease. A possible mechanism is discussed.